Development of Interactive Media Based on Quizizz paper Mode in IPAS learning In Grade IV of Elementary School - Fitrah Insani; Ardipal Ardipal; Zelhendri Zen; Leni Zahara (FKIP - Universitas Riau, 2026)
This study aims to develop, validate, and evaluate the practicality and effectiveness of Quizizz Paper Mode as an interactive learning medium for fourth-grade Ilmu Pengetahuan Alam dan Sosial (IPAS) in elementary schools. The research employed the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observations, interviews, expert validation sheets, practicality questionnaires, and learning outcome assessments. The study was conducted in three elementary schools: SDN 07, SDN 02, and SDN 16 Sungai Aur. Validation results from media, material, and language experts produced an average score of 90%, categorizing the media as very valid. Practicality tests involving teachers and students indicated high usability with percentages ranging from 92.5% to 95%. Effectiveness was measured through pre-test and post-test results analyzed using the N-Gain formula, showing substantial improvements with N-Gain scores of 0.77, 0.80, and 0.89, all classified as high. The findings demonstrate that Quizizz Paper Mode is valid, practical, and effective in improving student engagement, motivation, and understanding in IPAS learning. It is recommended as an interactive learning tool to support meaningful learning experiences in elementary schools.